Ukraińcy w ruchu rewolucyjnym w II Rzeczypospolitej - Cimek, Henryk (Zeszyty Wiejskie, 2012)
Following the end of the Polish-Soviet war and the conclusion of the Riga Treaty as of March 18 in 1921, Galicja (Małopolska) Wschodnia [Eastern Galicia (Little Poland)] was placed within the boundaries of the Polish state. The province’s national composition was mixed, whereby the Rusyn population (Ukrainian) prevailed over the Polish one. In about 90% it was a rural region, with a very high share of illiterate people which reached almost 80% in the case of Ukrainians. The Ukrainians constituted 14,3% of Poland’s population according to the national census of 1921 and 13,9% according to the census of 1931. Initially, those where the areas where Komunistyczna Partia Galicji Wschodniej [Communist Party of Eastern Galicia] was active (since February 1919), and then Komunistyczna Partia Zachodniej Ukrainy [Communist Party of Western Ukraine] (since October 1923) which was an autonomous district organization of Komunistyczna Partia Polski [Communist Party of Poland]. There were also legal Ukrainian revolutionary organizations, inter alia, Sel-Rob Jedność [Sel-Rob Unity]. The relations between Polish and Ukrainian communists were not very good, especially at the beginning, which is particularly focused upon in the present paper.